Małżeństwo i rodzina w etyce religijnej świadków Jehowy - Chojnacka, Gracjana (Wydawnictwo Naukowe UAM, 2007)
The aim of this paper is to present a sociological analysis of roles, social positions and family interactions as imposed by standards and principles used in families of the religious organization called Jehovah's Witnesses. When analyzing religious morality obligatory for Jehovah's Witnesses, we can see numerous connections between family and God. Everything referring to family life should be an expression of love and respect to God. If the principles given by God in the Bible are used for family life, it is possible to enter into close spiritual relations with Him. Jehovah's Witnesses treat the Bible as a source of standards and principles describing the model of marriage, regulating sexual life, deciding about distribution of roles in family hierarchy, giving guidelines as to education of children, as to divorces or legal separation. In the present world that accepts new morality and rejects marriage as being time-worn, Jehovah's Witnesses stick to their set of religious principles defining the form of family life. They are determined not to submit to factors affecting transformation of marriage. They believe that it is possible to create a happy family life even if the contemporary family model is in crisis.
Marriage and family in the religious ethics of Jehova's Witnesses